2018
DOI: 10.1101/445114
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Epigenetic drift during long-term culture of cells in vitro

Abstract: Replicative senescence of cells in culture is associated with highly reproducible DNA methylation (DNAm) changes at specific sites in the genome. Thus far, it is largely unclear if these epigenetic modifications are directly regulated, or if they are randomly evoked by other chromatin changes during long-term culture.We have identified CG dinucleotides (CpGs) that become continuously hyper-or hypomethylated in the course of culture expansion of mesenchymal stem cells (MSCs) and other cell types. These modifica… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 75 publications
(82 reference statements)
2
6
0
Order By: Relevance
“…Furthermore, our analysis of DNAm patterns in individual reads of BBA-seq demonstrated that neighboring CpGs are modified rather independently. We have recently described similar findings for DNAm changes during long-term culture of cells in vitro (Franzen et al 2017;Franzen et al 2018). While the stochastic changes at neighboring CpGs challenge the view of directed regulation of age-associated DNAm, they may support the notion that this process is evoked by "epigenetic drift", possibly caused by changes in chromatin conformation.…”
Section: Discussionsupporting
confidence: 71%
“…Furthermore, our analysis of DNAm patterns in individual reads of BBA-seq demonstrated that neighboring CpGs are modified rather independently. We have recently described similar findings for DNAm changes during long-term culture of cells in vitro (Franzen et al 2017;Franzen et al 2018). While the stochastic changes at neighboring CpGs challenge the view of directed regulation of age-associated DNAm, they may support the notion that this process is evoked by "epigenetic drift", possibly caused by changes in chromatin conformation.…”
Section: Discussionsupporting
confidence: 71%
“…Furthermore, our analysis of DNAm patterns in individual reads of BBA-seq demonstrated that neighboring CpGs are modified rather independently. We have recently described similar findings for DNAm changes during long-term culture of cells in vitro [29,60]. While the stochastic changes at neighboring CpGs challenge the view of directed regulation of age-associated DNAm, they may support the notion that this process is evoked by "epigenetic drift," possibly caused by changes in chromatin conformation.…”
Section: Discussionsupporting
confidence: 62%
“…Various genomic regions become continuously hyper-or hypomethylated during culture expansion [14,15]. We have previously shown that these modifications are independently acquired at neighboring CG dinucleotides (CpGs) [16,17]. A predominant DNA methylation pattern may, therefore, reveal the prevalence of dominant subclones [18].…”
Section: Introductionmentioning
confidence: 99%